On the self-dependence of the working classes under the law of competition - Leslie, T.E. Cliffe (Dublin Statistical Society, 1851)
The view which I take is opposed to the opinions of some distinguished writers, among whom I regret to place Mr. John Stuart Mill. In various forms, through his work upon the "Elements of Political Economy," I find theories contradictory to two propositions which appear to me to be cleaily demonstrable; viz. that in the absence of interference with economic laws, the productiveness of labor has no assignable limit; and that the natural laws of distribution are more favourable to the amount of the laborer's proportion of the produce, than any artificial regulations which can be devised, either by the legislature or by the laborers themselves.
Read April 29th 1851
Keywords: John Stuart Mill; Working classes; 314.15